Validation of molecular markers associated with boron tolerance, powdery mildew resistance and salinity tolerance in field peas - Javid, Muhammad; Rosewarne, Garry M.; Sudheesh, Shimna; Kant, Pragya; Leonforte, Antonio; Lombardi, Maria; Kennedy, Peter R.; Cogan, Noel O. I.; Slater, Anthony T.; Kaur, Sukhjiwan (Frontiers in Plant Science, 2015)
Field pea (Pisum sativum L.) is an important grain legume consumed both as human food and animal feed. However, productivity in low rainfall regions can be significantly reduced by inferior soils containing high levels of boron and/or salinity. Furthermore, powdery mildew (Erysiphe pisi) disease also causes significant yield loss in warmer regions. Breeding for tolerance to these abiotic and biotic stresses are major aims for pea breeding programs and the application of molecular markers for these traits could greatly assist in developing improved germplasm at a faster rate. The current study reports the evaluation of a near diagnostic marker, PsMlo, associated with powdery mildew (PM) resistance and boron (B) tolerance as well as linked markers associated with salinity tolerance across a diverse set of pea germplasm. The PsMlo1 marker predicted the PM and B phenotypic responses with high levels of accuracy (>80%) across a wide range of field pea genotypes, hence offers the potential to be widely adapted in pea breeding programs. In contrast, linked markers for salinity tolerance were population specific, therefore, application of these markers would be suitable to relevant crosses within the program. Our results also suggest that there are possible new sources of salt tolerance present in field pea germplasm that could be further exploited.